2010
DOI: 10.1117/12.848405
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of line-edge roughness (LER) propagation from resists: underlayer interfaces in ultrathin resist films

Abstract: Line edge roughness evolutions in EUV resist patterns are investigated. Three dimensional scanning electron microscopy images show the pattern sidewall roughness to be highly anisotropic and the roughness to be propagating from the resistsubstrate interface up the resist pattern sidewall. In ultrathin resist films, (film thickness ca. 100 nm and below) roughness is found to be fully correlated from the resist-substrate interface to the resist-air interface. This behavior is seen regardless of the resist platfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…[1][2][3][4] While the theoretical limitations to the RLS trade-off have been well documented, 5,6 this work has all been done at constant film thicknesses. An additional aspect of the RLS trade-off exists that has not been accounted for in these theoretical treatments: as resolution improves, the thickness of resists must concomitantly decrease to prevent line collapse.…”
Section: Introduction 11 Thin-film Ler Problemmentioning
confidence: 99%
“…[1][2][3][4] While the theoretical limitations to the RLS trade-off have been well documented, 5,6 this work has all been done at constant film thicknesses. An additional aspect of the RLS trade-off exists that has not been accounted for in these theoretical treatments: as resolution improves, the thickness of resists must concomitantly decrease to prevent line collapse.…”
Section: Introduction 11 Thin-film Ler Problemmentioning
confidence: 99%
“…LWR deteriorates as the photosensitivity is enhanced. Others have also reported high EUV photosensitivity with metal oxide nanoparticle containing photoresists or underlayers [11][12][13]. The metal oxides help generate more secondary electrons from the EUV radiation.…”
Section: Euv Photosensitivity Improvement By Mhmmentioning
confidence: 99%
“…Looking at the details of the resist to substrate interface [17], has also suggested that interface properties may be playing a significant role in LER and thus that underlayers might be able to mitigate these effects. Figure 2 shows an off-axis view of features in a leading EUV resist demonstrating a significant increase in LER at the resist to substrate interface and large anisotropy in the spatial scaling characteristics of the LER.…”
Section: Interface Effectsmentioning
confidence: 99%